Intra-serotype variation of Streptococcus pneumoniae capsule and its quantification - Hannes Eichner; Cindy Wu; Michael Cammer; Elizabeth N. H. Tran; Timothy R. Hirst; James C. Paton; Jeffrey N. Weiser (Microbiology Spectrum)
ABSTRACT Streptococcus pneumoniae (Spn) is a leading respiratory pathogen that depends on a thick layer of capsular polysaccharide (CPS) to evade immune clearance. Disease prevention by CPS-based vaccines is limited because of the species’ high genome plasticity and ability to express over 100 different capsule types (serotypes). Generally, intra-serotype variations in capsulation are overlooked, despite the genetic variability of the bacterium. This oversight may result from a lack of standardized, reliable, and easily available methodology to quantify capsulation. Here, we have modified two methods to analyze the Spn capsule: immunoblot quantification of CPS in bacterial lysates and light microscopy to assess capsule thickness. Two assays were used because each measures distinct aspects of capsulation that could be differentially affected by the density of CPS. Quantification of either CPS amount or capsule thickness predicted the effectiveness of immune serum in opsonophagocytic killing assays for isogenic strains. Our standardized approaches both revealed significant differences in both CPS amount and capsule thickness among clinical isolates of the same serotype, challenging the assumption that intra-serotype capsulation is a conserved feature. As expected, these two methods show limited intra-strain correlation between amounts of CPS production and capsule thickness.IMPORTANCEDespite the availability of vaccines, Streptococcus pneumoniae remains a leading cause of respiratory and invasive diseases. These vaccines target a polysaccharide capsule the bacterium uses to evade the immune system. Variation of the capsule composition subdivides the organism into serotypes and influences its protective potency. Another critical factor affecting this protection is capsule size. It is commonly assumed that S. pneumoniae strains of the same serotype produce capsules of consistent size, despite the organism’s heterogeneity. In this study, we challenge this assumption by analyzing clinical isolates of the same serotype. Existing methods were modified to achieve high reproducibility and increase accessibility. Our data reveal significant fluctuations in capsule production within a given serotype. Our findings suggest that S. pneumoniae research should consider capsule size, not just its presence and type. The results imply that standardized vaccine efficacy tests may yield variable results depending on the capsule production of target strains.